(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация:В статье рассматриваются основные аспекты межкультурной коммуникации и лингвокультурологии как взаимосвязанных дисциплин, изучающих влияние культуры на процессы общения. Анализируется роль языка как носителя культурных ценностей и национальной идентичности, а также особенности взаимодействия представителей разных лингвокультурных сообществ. Annotation: The article examines the main aspects of intercultural communication and linguacultural studies as interrelated disciplines that study the influence of culture on communication processes. The role of language as a carrier of cultural values and national identity, as well as the features of interaction between representatives of different linguacultural communities, are analyzed.